The determinants of poverty transitions in Europe and the role of duration dependence - Eirini Andriopoulou; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2011)
The paper examines the mobility into and out of poverty and identifies the determinants of poverty spell beginnings and endings in 14 European Countries for the period 1994-2000, using the European Community Household Panel. The first part of the paper offers a snapshot of poverty mobility in Europe calculating the entry and exit poverty rates, along with the conditional, to the duration of spell, exit probabilities and re-entry rates to poverty. In the second part observed characteristics of the household and the household head are examined in order to identify the determinants of the transitions into and out of poverty, taking into account unobserved heterogeneity across individuals and duration dependence. Multivariate discrete hazard analysis is used and the duration dependence is captured with time dummies. In almost all the 14 EU Member-States examined, the probability of exiting (re-entering) poverty is inversely related to the duration of the poverty (non-poverty) spell. The effect is significant to the inclusion of variables capturing observed heterogeneity (socioeconomic characteristics of the household head and the household and particular employment and demographic events), as well as to the inclusion of a random effects factor capturing the unobserved heterogeneity across individuals. With regards to the socio-economic variables, in most countries, households headed by young or elderly individuals, as well as households with dependent children are in higher risk of staying longer in poverty. In many cases, event variables improve the model significantly and highlight the mechanisms that bring individuals into and out of poverty.
urn:nbn:de:101:1-201105173282
Keywords: I32; I38; 330; poverty dynamics; EU